Research Study on Factors and Strategies to Impart Employability Skills of College students in Tamil Nadu - Murugan, Dr.M.Sakthivel; S.Sekar; Dr.T.Sujatha; Dr. M. Anbuselvi (The journal of contemporary issues in business and government, 2021)
Employability skills are essential for acquiring and pursuing goals of college students for their employment in the corporate sector. Educational institutions with the help of their teachers make all out effort to impart knowledge of employability. This study is aimed at factors and strategies which are vital for students employability in the Indian corporate sector.